Effects of arm truncation on the appearance of the halo artifact in 68Ga-PSMA-11 (HBED-CC) PET/MRI - Afshar-Oromieh, Ali; Wolf, Maya Barbara; Haberkorn, Uwe; Kachelrieß, Marc; Gnirs, Regula; Kopka, Klaus; Schlemmer, Heinz-Peter; Freitag, Martin T. (European journal of nuclear medicine and molecular imaging, 2017)
PurposePSMA ligand imaging with hybrid PET/MRI scanners could be an integral part of the clinical routine in the future. However, the first study about this novel method revealed a severe photopenic artifact (“halo artifact”) around the urinary bladder causing significantly reduced tumor visibility. The aim of this evaluation was to analyze the role of arm truncation on the appearance of the halo artifact in 68Ga-PSMA-11 PET/MRI hypothesizing that this influences the appearance.MethodsTwenty-seven consecutive patients were subjected to 68Ga-PSMA-11 PET/CT (1 h p.i.) followed by PET/MRI (3 h p.i.). PET/MRI was first started with scans of the abdomen to pelvis with arms positioned up above the head. Immediately thereafter, additional scans from the pelvis to abdomen were conducted with arms positioned down beside the trunk. All investigations were first analyzed separately and then compared with respect to tumor detection and tumor uptake (SUV) as well as the presence and intensity of the halo artifact. The Wilcoxon signed rank test was used to determine statistical differences including Bonferroni correction.ResultsThe halo was significantly reduced if the arms were elevated. Lesions inside the halo artifact (n = 16) demonstrated significantly increased SUVmean (p = 0.0007) and SUVmax (p = 0.0024) with arms positioned up. The halo appearance and intensity was not dependent on the total activity and activity concentration of the urinary bladder.ConclusionPositioning the arms down was shown to be significantly associated with the appearance of the halo artifact in PET/MRI. Positioning the arms up above the head can significantly reduce the halo artifact, thereby detecting more tumor lesions.
Die Zahl 68 ist im Titel hochgestellt
Gesehen am 13.12.2018